Nitrogen metabolism in tomato – Fusarium solani host pathogen system - M. PRASAD, M. SAXENA and (Indian Phytopathology, 2002)
Investigation of pre- and post-emergence damping off of two cultivars of tomato Marglobe and Pusa Ruby show that the metabolism of host plants is greatly affected by in vivo activity of proteolytic enzyme of Fusarium solani. The enzyme action affects qualitative and quantitative changes in total amino acids and protein content of the tomato seedlings. Profuse proteolytic enzyme activity, high level total amino acid output and low protein content can be correlated with the susceptibility of the host.